ANALISIS PERILAKU IMPULSE BUYING KONSUMEN MUSLIM DI PURWOKERTO PADA PLATFORM DIGITAL BERDASARKAN TEORI STIMULUS-ORGANISME-RESPONS (SOR) - Natasya Herliani; Sekar Maulida Putri; Wulan Linda Puspita Sari; Mahardika Cipta Raharja; Rini Meliana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This qualitative research aims to analyze the impulse buying behavior of Muslim consumers in Purwokerto on a digital platform using the Stimulus-Organism-Response (SOR) theory framework. The research results show that external stimulus which includes visual appeal of products, aggressive promotions such as flash sales, and the ease of digital payment systems are the main triggers for spontaneous shopping. At the organism stage, the consumer's internal process that involves positive emotions and price perception often ignores the mechanism of self-control and Islamic values such as the principle of qana'ah and the prohibition of israf. In response, consumers make unplanned purchases that produce various post-purchase emotions, both in the form of satisfaction and regret. This research concludes that strengthening shopping planning and internalization of the value of Islamic simplicity is very important to control consumptive behavior in the digital era